Qualitative analysis of stroke patients' motivation for rehabilitation. Issue 7268 (28th October 2000) - Maclean, Niall; Pound, Pandora; Wolfe, Charles; Rudd, Anthony
Abstract: Objective: To explore the attitudes and beliefs of stroke patients identified by professionals as having either "high" or "low" motivation for rehabilitation. Design: Qualitative study with semistructured interviews. Setting: The stroke unit of an inner city teaching hospital. Participants: 22 patients with stroke who were undergoing rehabilitation; 14 with high motivation for rehabilitation and eight with low motivation. Results: All patients thought rehabilitation was important for recovery. High motivation patients were more likely to view rehabilitation as the most important means of recovery and to accord themselves an active role in rehabilitation. These patients were also more likely to understand rehabilitation and in particular to understand the specialist role of the nursing staff. Many patients reported independence at home as a personal goal, though few low motivation patients related this goal to success in rehabilitation. Information from professionals about rehabilitation, favourable comparisons with other stroke patients, and the desire to leave hospital had a positive effect on motivation. Conversely, overprotection from family members and professionals, lack of information or the receipt of "mixed messages" from professionals, and unfavourable comparisons with other patients had a negative effect. Conclusions: There are some differences in beliefs between stroke patients identified as having low or high motivation for rehabilitation. These beliefs seem to be influenced by the environment in which the patient is rehabilitated. Professionals and carers should be made aware of the ways in which their behaviour can positively and negatively affect motivation.